The Phenomenon of Knowledge Hiding in the Perspective of Today's Market Challenges - Literature Review and Research Concept - Anita PROSZOWSKA (Communications of International Proceedings, 2021)
As part of this study, the phenomenon of knowledge hiding has been characterised, and it was described how its occurrence influences the functioning of entire enterprises and their employees.  The analysis assumes that properly using available information and managing the knowledge generated professionally is becoming increasingly crucial for the modern economy. Therefore, the awareness of knowledge processes in the economy is so important. And while knowledge management or knowledge sharing is described in detail both in the world and Polish literature, knowledge hiding practically does not exist in Polish research publications. Therefore, this paper attempts to systematise this topic. The analysis of research theses and the results of this phenomenon on foreign markets allowed the author to create her model of behaviours related to the knowledge processes of a given entity within the organisation, helping to monitor employee behaviours related to knowledge hiding and sharing. Finally, empirical research verifying the shape of this model as part of the Polish reality and the isolation of variables that would have the most significant impact on knowledge hiding phenomenon were proposed. The paper contains the summary taking into account the analysis of development perspectives of the knowledge sharing and hiding process in the light of emerging trends, such as data driven development on the one hand or commoditisation on the other.
Keywords: Knowledge hiding; knowledge management; information; knowledge sharing.